Corporate Social Responsibility, Sustainable Business Strategies, and Profitability: A Literature Review - Angelica Boniera Tampubolon; Keran Yohanan Manao; Rafika Susanti; Raihan Ammar Saleh (Global Research on Economy, Business, Communication, and Information, 2025)
In today's business world, companies are not only required to make profits, but also to be responsible to the community and the environment. One form of this responsibility is through the implementation of  Corporate Social Responsibility (CSR). This study aims to determine the role of CSR as a sustainable business strategy in increasing company profitability. The research method used is a qualitative approach with a literature study, namely reviewing various journals related to CSR, sustainable business strategies, and profitability.